Endogenously released GIP reduces and GLP-1 increases hepatic insulin extraction - Keyhani-Nejad, Farnaz; Barbosa Yanez, Renate Luisa; Kemper, Margrit; Schueler, Rita; Pivovarova-Ramich, Olga; Rudovich, Natalia; Pfeiffer, Andreas F.H. (Peptides (New York, N.Y. : 1980), 2020)
•The induction of fatty liver and insulin resistance by sucrose requires GIP receptors and is prevented by the similarly composed but distally absorbed glucose-fructose dimer, isomaltulose, which releases little GIP but much GLP-1.•Hepatic insulin clearance is improved in humans by isomaltulose as compared to sucrose which correlates with a reduced GIP and increased GLP-1 response.•The most likely mechanism is a regulation of hepatic perfusion by GIP which was shown previously in fluoro-deoxy-glucose (FDG)-PET-Scans in humans as well as by GIP-receptors in the portal vein and hepatic arteries.•We therefore propose that GIP regulates hepatic insulin extraction and action. GIP was proposed to play a key role in the development of non- alcoholic fatty liver disease (NAFLD) in response to sugar intake. Isomaltulose, is a 1,6-linked glucose-fructose dimer which improves glucose homeostasis and prevents NAFLD compared to 1,2-linked sucrose by reducing glucose-dependent insulinotropic peptide (GIP) in mice. We compared effects of sucrose vs. isomaltulose on GIP and glucagon-like peptide-1 (GLP-1) secretion, hepatic insulin clearance (HIC) and insulin sensitivity in normal (NGT), impaired glucose tolerant (IGT) and Type 2 diabetes mellitus (T2DM) participants. A randomized crossover study was performed in 15 NGT, 10 IGT and 10 T2DM subjects. In comparison to sucrose, peak glucose concentrations were reduced by 2.3, 2.1 and 2.5 mmol/l (all p < 0.05) and insulin levels were 88% (p < 0.01, NGT), 32% (p < 0.05, IGT) and 55% (T2DM) lower after the isomaltulose load. Postprandial GIPiAUC concentrations were decreased (56%, p < 0.01 in NGT; 42%, p < 0.05 in IGT and 40%,p < 0.001 in T2DM) whereas GLP-1iAUC was 77%, 85% and 85% higher compared to sucrose (p < 0.01), respectively. This resulted in ∼35 - 50% improved insulin sensitivity and reduced insulinogenic index after isomaltulose, which correlated closely with improved HIC, respectively (r = 0.62, r=-0.70; p < 0.001). HIC was inversely related to GIP (r=-0.44, p < 0.001) and positively related to GLP-1 levels (r = 0.40, p = 0.001). Endogenously released GIP correlated with reduced, and GLP-1 with increased hepatic insulin extraction. Increased peripheral insulin levels may contribute to insulin resistance and obesity. We propose that the unfavorable effects of high glycemic index Western diets are related to increased GIP-release and reduced HIC.